2000
DOI: 10.1046/j.1365-2508.2000.00319.x
|View full text |Cite
|
Sign up to set email alerts
|

The value of outpatient hysteroscopy in the management of postmenopausal bleeding: a review of 862 cases

Abstract: Objective To evaluate the efficacy, reliability and acceptability of outpatient hysteroscopy in the investigation of postmenopausal bleeding in a major teaching hospital. Design A retrospective descriptive study of 862 women referred with postmenopausal bleeding for outpatient hysteroscopy. Methods Between 1994 and 1997, 862 women were referred to the Women's Endoscopy Unit at Nottingham City Hospital for postmenopausal bleeding. Of these women, 171 were receiving hormone replacement treatment. The endocervica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
1
7
2
Order By: Relevance
“…However, in relation to normal histologic diagnosis we found 8%-12% less than that found in other studies (26)(27)(28).…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…However, in relation to normal histologic diagnosis we found 8%-12% less than that found in other studies (26)(27)(28).…”
Section: Discussioncontrasting
confidence: 79%
“…Nevertheless, this smaller number of normal results, in comparison with those reported in other studies, occurred with the histologic diagnosis, but not with the hysteroscopic findings (26)(27)(28). The fact that our prevalence of endometrial polyp is within the same range as that of those studies (10%-33%), suggests that there was an increase in the diagnoses of other bleeding-related pathologies.…”
Section: Discussioncontrasting
confidence: 75%
“…However, it is also useful in malignancies, in that it makes direct biopsies possible [1,6,7,13,14]. Such an examination may be conducted on outpatients, without anaesthesia, allowing in most cases a complete view of the uterine cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Hysteroscopy allows a direct view of the endometrium, and biopsies are also possible [1,13,14]. It permits an accurate macroscopic diagnosis of benign lesions and their removal, allowing a ‘see and treat' approach, but histological samples must always be taken [1,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Based on our study, the relative risk of a postmenopausal woman presenting to a hysteroscopy clinic with abnormal bleeding caused by endometrial cancer is more than 10 times that of an HRT user. Two previous similar smaller studies examining hysteroscopy data failed to find a significant difference between the two groups (2,17). Importantly, in our study 13 of these cases were identified in early stages, 11 at stage I, and two at stage II; the other patient declined treatment and was not formally staged.…”
Section: Discussionmentioning
confidence: 78%